Hot-dip galvanizing layer for cable bridge and preparation method of hot-dip galvanizing layer

By adopting a specific composition of hot-dip galvanized layer on the cable tray and combining microarc oxidized electrolyte and nanotitanium dioxide treatment, the problem of insufficient corrosion resistance and durability of the traditional hot-dip galvanized process on the cable tray is solved, and higher wear resistance and pollution resistance are achieved, ensuring the safety and stability of power transmission.

CN119876810APending Publication Date: 2025-04-25TENGZHOU HENGDA CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510070594.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-16
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

The traditional hot-dip galvanizing process has problems such as uneven thickness, many impurities, and insufficient corrosion resistance and durability on the cable tray, making it difficult to meet the high-standard protection needs.

Method used

A hot-dip galvanized layer including 40-60 parts of zinc, 2-8 parts of aluminum, 1-5 parts of magnesium, 1-3 parts of rare earth elements, 10-20 parts of ammonium chloride, 2-6 parts of additives, and 5-10 parts of refining agent is adopted. A ceramic film is grown on the surface of the galvanized layer by microarc oxidation electrolyte electrolytic process, and treated with nanotitanium dioxide and aminosilane coupling agent to improve wear resistance and stain resistance.

Benefits of technology

The thickness uniformity and toughness of the galvanized layer are achieved, which significantly improves wear resistance and pollution resistance, can effectively resist environmental erosion and physical wear, reduce the maintenance frequency of cable trays, and ensure the safety of power transmission.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to the technical field of metal surface coatings, and discloses a hot-dip galvanizing layer for a cable bridge and a preparation method thereof, the hot-dip galvanizing layer comprises the following components by weight: 40-60 parts of zinc, 2-8 parts of aluminum, 1-5 parts of magnesium, 1-3 parts of rare earth element, 10-20 parts of ammonium chloride, 2-6 parts of an auxiliary agent, and 5-10 parts of a refining agent. Through a micro-arc oxidation electrolyte electrolysis process, a ceramic membrane grows on the surface of a zinc coating in situ, and meanwhile, nano titanium dioxide is adopted for treatment, so that the wear resistance is greatly improved. An amino silane coupling agent is selected for treatment, one end of a silane molecule is chemically bonded with a zinc layer, a hydrophobic barrier is constructed by an organic group at the other end, and the anti-pollution capacity of the coating is improved. When the hot-dip galvanizing layer material produced by the preparation method is used for the cable bridge, the thickness uniformity of a galvanizing layer and the toughness of the galvanizing layer are good, the environmental erosion and physical wear can be effectively resisted, the maintenance frequency of the cable bridge is reduced, and the power transmission safety is guaranteed.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of metal surface coatings, in particular to a hot-dip galvanized layer for a cable bridge and a preparation method thereof. Background Art

[0002] Cable trays are key facilities to ensure the orderly laying of electrical lines. They are exposed to outdoor or complex indoor environments for a long time, and are subject to multiple corrosions such as humidity, acid rain, industrial waste gas, and ultraviolet rays. They require extremely high corrosion resistance and durability. Although the traditional hot-dip galvanizing process can provide a certain degree of protection, the galvanized layer is prone to problems such as uneven thickness, more impurities, and insufficient corrosion resistance and durability. It is difficult to meet the current high-standard protection requirements of cable trays, and it is urgent to develop an improved hot-dip galvanizing layer material preparation method. Summary of the invention

[0003] 1. Technical issues to be solved

[0004] In view of the deficiencies in the prior art, the present invention provides a hot-dip galvanized layer for a cable bridge and a preparation method thereof.

[0005] (II) Technical solution

[0006] A hot-dip galvanized layer for a cable tray, comprising the following weight components:

[0007] 40-60 parts of zinc, 2-8 parts of aluminum, 1-5 parts of magnesium, 1-3 parts of rare earth elements, 10-20 parts of ammonium chloride, 2-6 parts of additives, and 5-10 parts of refining agents.

[0008] Preferably, the zinc is made of high-purity zinc ingots with a purity higher than 99.99% as raw material.

[0009] Preferably, the rare earth element is one or more of cerium, lanthanum, praseodymium and neodymium.

[0010] Preferably, the auxiliary agent is a dispersant, a defoamer and a leveling agent in a mass ratio of 1:1:1; the dispersant is one of polyethylene glycol, lignin sulfonate or fatty amine polyoxyethylene ether; the defoamer is dimethyl silicone oil; and the leveling agent is polyurethane.

[0011] Preferably, the refining agent is one or more of sodium fluoride, calcium fluoride, sodium carbonate or borax.

[0012] Preferably, the method comprises the following steps:

[0013] S1. Put zinc ingot, aluminum, magnesium and rare earth elements into the furnace according to weight, first heat it to 450-500℃ to make the raw materials melt initially, stir at a low speed of 100-150r / min for 10-15min, then heat it to 550-600℃, add ammonium chloride, additives and refining agent, stir at a high speed of 300-400r / min for 20-30min to obtain hot-dip galvanizing liquid;

[0014] S2. Put the cable tray into the degreasing liquid, soak it at 50-60℃ for 15-25min, rinse it with clean water until it becomes neutral, then immerse it in a hydrochloric acid solution with a mass fraction of 15-20%, pickle it at room temperature for 8-15min, rinse it with clean water, then neutralize it in a dilute sodium carbonate solution with a mass fraction of 1-2% for 3-5min, finally rinse it with clean water and dry it;

[0015] S3, the cable bridge treated in step S2 is quickly immersed in a hot-dip galvanizing solution at 440-460° C. for 30-90 seconds;

[0016] S4. After the galvanizing is completed, the cable tray is placed in a micro-arc oxidation electrolyte, with the cable tray as the anode and the stainless steel plate as the cathode. Under a specific pulse power supply, a voltage of 300-500V is applied for 5-15 minutes;

[0017] S5. The cable tray treated in step S4 is sent to a plasma treatment device, and the treatment is performed for 3-5 minutes at a power of 100-200 W under an argon atmosphere;

[0018] S6, mixing nano titanium dioxide and aminosilane coupling agent to prepare an ethanol solution with a mass fraction of 5-10%, immersing the cable bridge treated in step S5 at 30-60° C. for 30-60 min, and finally treating at 180-220° C. for 2-3 h;

[0019] S7. Rinse the cable tray treated in step S6 with clean water, then put it into the passivation solution, soak it at room temperature for 2-3 minutes, dry it at 60-80° C. for 1-2 hours, and then age it at 150-200° C. for 3-5 hours.

[0020] Preferably, the degreasing liquid in step S2 is a sodium hydroxide solution with a mass fraction of 8-12%.

[0021] Preferably, in step S3, an ultrasonic device with a frequency of 20-60 kHz is turned on during the immersion plating.

[0022] Preferably, in step S6, the mass ratio of nano-titanium dioxide to aminosilane coupling agent is 1:1.

[0023] Preferably, the passivation solution in step S6 is a solution containing 3-5% by mass of sodium chromate and 1-2% by mass of sodium phosphate.

[0024] (III) Beneficial technical effects

[0025] A hot-dip galvanized layer for a cable bridge comprises the following components by weight: 40-60 parts of zinc, 2-8 parts of aluminum, 1-5 parts of magnesium, 1-3 parts of rare earth elements, 10-20 parts of ammonium chloride, 2-6 parts of additives, and 5-10 parts of refining agents.

[0026] Through the micro-arc oxidation electrolyte electrolysis process, a ceramic film is grown in situ on the surface of the zinc coating, and nano-titanium dioxide is used for treatment, which greatly improves the wear resistance. Aminosilane coupling agent is used for treatment, and one end of the silane molecule is chemically bonded to the zinc layer, and the organic group at the other end constructs a hydrophobic barrier to improve the anti-fouling ability of the coating. When the hot-dip galvanized layer material produced by this preparation method is used for cable trays, the zinc coating has uniform thickness and good toughness, which can effectively resist environmental erosion and physical wear, reduce the maintenance frequency of cable trays, and ensure the safety of power transmission. DETAILED DESCRIPTION

[0027] Example 1

[0028] S1. 40 parts by weight of zinc ingot, 2 parts by weight of aluminum, 1 part by weight of magnesium and 1 part by weight of rare earth element are put into a melting furnace according to their weight. The temperature is first raised to 450°C to initially melt the raw materials. During this period, the raw materials are stirred at a low speed of 100 r / min for 10 minutes. Then, the temperature is raised to 550°C, 10 parts by weight of ammonium chloride, 2 parts by weight of auxiliary agent and 5 parts by weight of refining agent are added, and the mixture is stirred at a high speed of 300 r / min for 20 minutes to obtain a hot-dip galvanizing liquid.

[0029] S2. Place the cable tray in an alkaline degreasing solution of 8% sodium hydroxide by mass, soak it at 50°C for 15 minutes, rinse it with clean water until it is neutral, then immerse it in a 15% hydrochloric acid solution by mass, pickle it at room temperature for 8 minutes, rinse it with clean water, then neutralize it in a dilute solution of 1% sodium carbonate by mass for 3 minutes, finally rinse it with clean water and dry it.

[0030] S3, the cable tray treated in step S2 is quickly immersed in a 440° C. hot-dip galvanizing solution for 30 seconds, during which an ultrasonic device with a frequency of 20 kHz is turned on.

[0031] S4. After galvanizing is completed, place the cable tray in a micro-arc oxidation electrolyte, with the cable tray as the anode and the stainless steel plate as the cathode. Under a specific pulse power supply, apply a voltage of 300V and treat for 5 minutes.

[0032] S5. The cable tray treated in step S4 is sent to a plasma treatment device under an argon atmosphere with a power of 100 W and treated for 3 minutes.

[0033] S6. Mix nano titanium dioxide and aminosilane coupling agent in a mass ratio of 1:1 to prepare an ethanol solution with a mass fraction of 5%, immerse the cable tray treated in step S5, soak at 30° C. for 30 minutes, and finally treat at 180° C. for 2 hours.

[0034] S7. Rinse the cable tray treated in step S6 with clean water, and then put it into a passivation solution containing 3% sodium chromate and 1% sodium phosphate by mass, soak it at room temperature for 2 minutes, dry it at 60° C. for 1 hour, and then age it at 150° C. for 3 hours.

[0035] Example 2

[0036] S1. 60 parts by weight of zinc ingot, 8 parts by weight of aluminum, 5 parts by weight of magnesium and 3 parts by weight of rare earth elements are put into a melting furnace according to weight. The temperature is first raised to 500°C to initially melt the raw materials, and stirred at a low speed of 150r / min for 15min. Then the temperature is raised to 600°C, 20 parts by weight of ammonium chloride, 6 parts by weight of auxiliary agent and 10 parts by weight of refining agent are added, and stirred at a high speed of 400r / min for 30min to obtain hot-dip galvanizing liquid.

[0037] S2. Place the cable tray in an alkaline degreasing solution of 12% sodium hydroxide by mass, soak it at 60°C for 25 minutes, rinse it with clean water until it is neutral, then immerse it in a 20% hydrochloric acid solution by mass, pickle it at room temperature for 15 minutes, rinse it with clean water, then neutralize it in a dilute sodium carbonate solution of 2% by mass for 5 minutes, finally rinse it with clean water and dry it.

[0038] S3, the cable tray treated in step S2 is quickly immersed in a 460° C. hot-dip galvanizing solution for 90 seconds, during which an ultrasonic device with a frequency of 60 kHz is turned on.

[0039] S4. After galvanizing is completed, place the cable tray in a micro-arc oxidation electrolyte, with the cable tray as the anode and the stainless steel plate as the cathode. Under a specific pulse power supply, apply a voltage of 500V and treat for 15 minutes.

[0040] S5. The cable tray treated in step S4 is sent to a plasma treatment device under an argon atmosphere with a power of 200 W set for treatment for 5 minutes.

[0041] S6. Mix nano titanium dioxide and aminosilane coupling agent in a mass ratio of 1:1 to prepare an ethanol solution with a mass fraction of 10%, immerse the cable tray treated in step S5, soak at 60° C. for 60 minutes, and finally treat at 220° C. for 3 hours.

[0042] S7. Rinse the cable tray treated in step S6 with clean water, and then put it into a passivation solution containing 5% sodium chromate and 2% sodium phosphate by mass, soak it at room temperature for 3 minutes, dry it at 80° C. for 2 hours, and then age it at 200° C. for 5 hours.

[0043] Example 3

[0044] S1. 45 parts by weight of zinc ingot, 3 parts by weight of aluminum, 2 parts by weight of magnesium and 2 parts by weight of rare earth elements are put into a melting furnace according to weight. The temperature is first raised to 500°C to initially melt the raw materials. During this period, the raw materials are stirred at a low speed of 120r / min for 15min. Then the temperature is raised to 550°C, 14 parts by weight of ammonium chloride, 5 parts by weight of auxiliary agent and 8 parts by weight of refining agent are added, and the mixture is stirred at a high speed of 400r / min for 20min to obtain a hot-dip galvanizing liquid.

[0045] S2. Place the cable tray in an alkaline degreasing solution with a mass fraction of 10% sodium hydroxide, soak it at 60°C for 20 minutes, rinse it with clean water until it is neutral, then immerse it in a hydrochloric acid solution with a mass fraction of 20%, pickle it at room temperature for 10 minutes, rinse it with clean water, then neutralize it in a dilute sodium carbonate solution with a mass fraction of 1.5% for 4 minutes, and finally rinse it with clean water and dry it.

[0046] S3. The cable tray treated in step S2 is quickly immersed in a 450° C. hot-dip galvanizing solution for 50 seconds, during which an ultrasonic device with a frequency of 50 kHz is turned on.

[0047] S4. After galvanizing is completed, place the cable tray in a micro-arc oxidation electrolyte, with the cable tray as the anode and the stainless steel plate as the cathode. Under a specific pulse power supply, apply a voltage of 400V and treat for 10 minutes.

[0048] S5. The cable tray treated in step S4 is sent to a plasma treatment device under an argon atmosphere with a power of 150 W and treated for 5 minutes.

[0049] S6. Mix nano titanium dioxide and aminosilane coupling agent in a mass ratio of 1:1 to prepare an ethanol solution with a mass fraction of 6%, immerse the cable tray treated in step S5, soak at 40° C. for 40 minutes, and finally treat at 200° C. for 2.5 hours.

[0050] S7. Rinse the cable tray treated in step S6 with clean water, and then put it into a passivation solution containing 4% sodium chromate and 1.2% sodium phosphate by mass, soak it at room temperature for 3 minutes, dry it at 80° C. for 1.5 hours, and then age it at 180° C. for 4 hours.

[0051] Example 4

[0052] S1. 50 parts by weight of zinc ingot, 5 parts by weight of aluminum, 4 parts by weight of magnesium and 3 parts by weight of rare earth elements are put into a melting furnace according to weight. The temperature is first raised to 500°C to initially melt the raw materials. During this period, the raw materials are stirred at a low speed of 100 r / min for 10 minutes. Then the temperature is raised to 600°C, 15 parts by weight of ammonium chloride, 3 parts by weight of auxiliary agent and 9 parts by weight of refining agent are added, and the mixture is stirred at a high speed of 300 r / min for 30 minutes to obtain a hot-dip galvanizing liquid.

[0053] S2. Place the cable tray in an alkaline degreasing solution of 9% sodium hydroxide by mass, soak it at 55°C for 25 minutes, rinse it with clean water until it is neutral, then immerse it in a hydrochloric acid solution of 18% by mass, pickle it at room temperature for 12 minutes, rinse it with clean water, then neutralize it in a dilute sodium carbonate solution of 2% by mass for 3 minutes, and finally rinse it with clean water and dry it.

[0054] S3, the cable tray treated in step S2 is quickly immersed in a 460° C. hot-dip galvanizing solution for 30 seconds, during which an ultrasonic device with a frequency of 40 kHz is turned on.

[0055] S4. After galvanizing, place the cable tray in a micro-arc oxidation electrolyte with the cable tray as the anode and the stainless steel plate as the cathode. Under a specific pulse power supply, apply a voltage of 450V and treat for 10 minutes.

[0056] S5. The cable tray treated in step S4 is sent to a plasma treatment device under an argon atmosphere with a power of 180 W and treated for 4 minutes.

[0057] S6. Mix nano titanium dioxide and aminosilane coupling agent in a mass ratio of 1:1 to prepare an ethanol solution with a mass fraction of 10%, immerse the cable tray treated in step S5, soak at 30° C. for 60 minutes, and finally treat at 220° C. for 2 hours.

[0058] S7. Rinse the cable tray treated in step S6 with clean water, and then put it into a passivation solution containing 5% sodium chromate and 1% sodium phosphate by mass, soak it at room temperature for 2 minutes, dry it at 70° C. for 1.5 hours, and then age it at 180° C. for 5 hours.

[0059] Example 5

[0060] S1. 55 parts by weight of zinc ingot, 6 parts by weight of aluminum, 3 parts by weight of magnesium and 1 part by weight of rare earth element are put into a melting furnace according to weight. The temperature is first raised to 480°C to initially melt the raw materials. During this period, the raw materials are stirred at a low speed of 140r / min for 15min. Then the temperature is raised to 580°C, 20 parts by weight of ammonium chloride, 5 parts by weight of auxiliary agent and 10 parts by weight of refining agent are added, and the mixture is stirred at a high speed of 400r / min for 30min to obtain a hot-dip galvanizing liquid.

[0061] S2. Place the cable tray in an alkaline degreasing solution with a mass fraction of 12% sodium hydroxide, soak it at 50°C for 15 minutes, rinse it with clean water until it is neutral, then immerse it in a hydrochloric acid solution with a mass fraction of 15%, pickle it at room temperature for 15 minutes, rinse it with clean water, then neutralize it in a dilute sodium carbonate solution with a mass fraction of 1% for 5 minutes, and finally rinse it with clean water and dry it.

[0062] S3, the cable tray treated in step S2 is quickly immersed in a 460° C. hot-dip galvanizing solution for 90 seconds, during which an ultrasonic device with a frequency of 30 kHz is turned on.

[0063] S4. After galvanizing is completed, place the cable tray in a micro-arc oxidation electrolyte, with the cable tray as the anode and the stainless steel plate as the cathode. Under a specific pulse power supply, apply a voltage of 400V and treat for 10 minutes.

[0064] S5. The cable tray treated in step S4 is sent to a plasma treatment device under an argon atmosphere with a power of 200 W set for treatment for 3 minutes.

[0065] S6. Mix nano titanium dioxide and aminosilane coupling agent in a mass ratio of 1:1 to prepare an ethanol solution with a mass fraction of 10%, immerse the cable tray treated in step S5, soak at 60° C. for 60 minutes, and finally treat at 180° C. for 2 hours.

[0066] S7. Rinse the cable tray treated in step S6 with clean water, and then put it into a passivation solution containing 3.5% sodium chromate and 2% sodium phosphate by mass, soak it at room temperature for 3 minutes, dry it at 80° C. for 2 hours, and then age it at 200° C. for 5 hours.

[0067] Comparative Example 1

[0068] S1. 40 parts by weight of zinc ingot, 2 parts by weight of aluminum, 1 part by weight of magnesium and 1 part by weight of rare earth element are put into a melting furnace according to their weight. The temperature is first raised to 450°C to initially melt the raw materials. During this period, the raw materials are stirred at a low speed of 100 r / min for 10 minutes. Then, the temperature is raised to 550°C, 10 parts by weight of ammonium chloride, 2 parts by weight of auxiliary agent and 5 parts by weight of refining agent are added, and the mixture is stirred at a high speed of 300 r / min for 20 minutes to obtain a hot-dip galvanizing liquid.

[0069] S2. Place the cable tray in an alkaline degreasing solution of 8% sodium hydroxide by mass, soak it at 50°C for 15 minutes, rinse it with clean water until it is neutral, then immerse it in a 15% hydrochloric acid solution by mass, pickle it at room temperature for 8 minutes, rinse it with clean water, then neutralize it in a dilute solution of 1% sodium carbonate by mass for 3 minutes, finally rinse it with clean water and dry it.

[0070] S3, the cable tray treated in step S2 is quickly immersed in a 440° C. hot-dip galvanizing solution for 30 seconds, during which an ultrasonic device with a frequency of 20 kHz is turned on.

[0071] S4, preparing an aminosilane coupling agent into an ethanol solution with a mass fraction of 5%, immersing the cable tray treated in step S3, soaking at 30° C. for 30 minutes, and finally treating at 180° C. for 2 hours.

[0072] S5. Rinse the cable tray treated in step S4 with clean water, and then put it into a passivation solution containing 3% sodium chromate and 1% sodium phosphate by mass, soak it at room temperature for 2 minutes, dry it at 60° C. for 1 hour, and then age it at 150° C. for 3 hours.

[0073] Comparative Example 2

[0074] S1. 40 parts by weight of zinc ingot, 2 parts by weight of aluminum, 1 part by weight of magnesium and 1 part by weight of rare earth element are put into a melting furnace according to their weight. The temperature is first raised to 450°C to initially melt the raw materials. During this period, the raw materials are stirred at a low speed of 100 r / min for 10 minutes. Then, the temperature is raised to 550°C, 10 parts by weight of ammonium chloride, 2 parts by weight of auxiliary agent and 5 parts by weight of refining agent are added, and the mixture is stirred at a high speed of 300 r / min for 20 minutes to obtain a hot-dip galvanizing liquid.

[0075] S2. Place the cable tray in an alkaline degreasing solution of 8% sodium hydroxide by mass, soak it at 50°C for 15 minutes, rinse it with clean water until it is neutral, then immerse it in a 15% hydrochloric acid solution by mass, pickle it at room temperature for 8 minutes, rinse it with clean water, then neutralize it in a dilute solution of 1% sodium carbonate by mass for 3 minutes, finally rinse it with clean water and dry it.

[0076] S3, the cable tray treated in step S2 is quickly immersed in a 440° C. hot-dip galvanizing solution for 30 seconds, during which an ultrasonic device with a frequency of 20 kHz is turned on.

[0077] S4. After galvanizing is completed, place the cable tray in a micro-arc oxidation electrolyte, with the cable tray as the anode and the stainless steel plate as the cathode. Under a specific pulse power supply, apply a voltage of 300V and treat for 5 minutes.

[0078] S5. Prepare nano-titanium dioxide into an ethanol solution with a mass fraction of 5%, immerse the cable bridge treated in step S4, soak at 30° C. for 30 minutes, and finally treat at 180° C. for 2 hours.

[0079] S6. Rinse the cable tray treated in step S5 with clean water, and then put it into a passivation solution containing 3% sodium chromate and 1% sodium phosphate by mass, soak it at room temperature for 2 minutes, dry it at 60° C. for 1 hour, and then age it at 150° C. for 3 hours.

[0080] Comparative Example 3

[0081] S1. 40 parts by weight of zinc ingot, 2 parts by weight of aluminum, 1 part by weight of magnesium and 1 part by weight of rare earth element are put into a melting furnace according to their weight. The temperature is first raised to 450°C to initially melt the raw materials. During this period, the raw materials are stirred at a low speed of 100 r / min for 10 minutes. Then, the temperature is raised to 550°C, 10 parts by weight of ammonium chloride, 2 parts by weight of auxiliary agent and 5 parts by weight of refining agent are added, and the mixture is stirred at a high speed of 300 r / min for 20 minutes to obtain a hot-dip galvanizing liquid.

[0082] S2. Place the cable tray in an alkaline degreasing solution of 8% sodium hydroxide by mass, soak it at 50°C for 15 minutes, rinse it with clean water until it is neutral, then immerse it in a 15% hydrochloric acid solution by mass, pickle it at room temperature for 8 minutes, rinse it with clean water, then neutralize it in a dilute solution of 1% sodium carbonate by mass for 3 minutes, finally rinse it with clean water and dry it.

[0083] S3, the cable tray treated in step S2 is quickly immersed in a 440° C. hot-dip galvanizing solution for 30 seconds, during which an ultrasonic device with a frequency of 20 kHz is turned on.

[0084] The wear resistance and hydrophobicity of Examples 1-5 and Comparative Examples 1-3 were tested, and the results are shown in Table 1.

[0085] Table 1

[0086] Group <![CDATA[Wear rate (×10 -5 mm 3 / Nm)]]> Contact angle Roll Angle Example 1 3.5 162° 9.5° Example 2 3.3 158° 9.3° Example 3 3.6 160° 9.3° Example 4 3.8 157° 8.9° Example 5 3.6 155° 8.7 Comparative Example 1 7.3 153° 8.5° Comparative Example 2 3.5 89° 3.6° Comparative Example 3 8.9 85° 3.3°

[0087] As can be seen from Table 1, Examples 1-5 have good wear resistance and hydrophobicity; Comparative Example 1 has poor wear resistance and good hydrophobicity; Comparative Example 2 has good wear resistance and poor hydrophobicity; Comparative Example 3 has poor wear resistance and hydrophobicity.

[0088] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A hot-dip galvanized layer for a cable tray, characterized in that: It consists of the following components by weight: 40-60 parts of zinc, 2-8 parts of aluminum, 1-5 parts of magnesium, 1-3 parts of rare earth elements, 10-20 parts of ammonium chloride, 2-6 parts of additives, and 5-10 parts of refining agents.

2. The hot-dip galvanized layer for a cable tray according to claim 1, characterized in that: The zinc is made of high-purity zinc ingots with a purity higher than 99.99%.

3. The hot-dip galvanized layer for a cable tray according to claim 1, characterized in that: The rare earth element is one or more of cerium, lanthanum, praseodymium and neodymium.

4. The hot-dip galvanized layer for a cable tray according to claim 1, characterized in that: The auxiliary agent is a dispersant, a defoamer and a leveling agent in a mass ratio of 1:1:1; the dispersant is one of polyethylene glycol, lignin sulfonate or fatty amine polyoxyethylene ether; the defoamer is dimethyl silicone oil; and the leveling agent is polyurethane.

5. The hot-dip galvanized layer for a cable tray according to claim 1, characterized in that: The refining agent is one or more of sodium fluoride, calcium fluoride, sodium carbonate or borax.

6. A method for preparing a hot-dip galvanized layer for a cable tray as claimed in claims 1 to 5, characterized in that: The following steps are involved: S1. Put zinc ingot, aluminum, magnesium and rare earth elements into the furnace according to weight, first heat it to 450-500℃ to make the raw materials melt initially, stir at a low speed of 100-150r / min for 10-15min, then heat it to 550-600℃, add ammonium chloride, additives and refining agent, stir at a high speed of 300-400r / min for 20-30min to obtain hot-dip galvanizing liquid; S2. Put the cable tray into the degreasing liquid, soak it at 50-60℃ for 15-25min, rinse it with clean water until it becomes neutral, then immerse it in a hydrochloric acid solution with a mass fraction of 15-20%, pickle it at room temperature for 8-15min, rinse it with clean water, then neutralize it in a dilute sodium carbonate solution with a mass fraction of 1-2% for 3-5min, finally rinse it with clean water and dry it; S3, the cable bridge treated in step S2 is quickly immersed in a hot-dip galvanizing solution at 440-460° C. for 30-90 seconds; S4. After the galvanizing is completed, the cable tray is placed in a micro-arc oxidation electrolyte, with the cable tray as the anode and the stainless steel plate as the cathode. Under a specific pulse power supply, a voltage of 300-500V is applied for 5-15 minutes; S5. The cable tray treated in step S4 is sent to a plasma treatment device, and the treatment is performed for 3-5 minutes at a power of 100-200 W under an argon atmosphere; S6, mixing nano titanium dioxide and aminosilane coupling agent to prepare an ethanol solution with a mass fraction of 5-10%, immersing the cable bridge treated in step S5 at 30-60° C. for 30-60 min, and finally treating at 180-220° C. for 2-3 h; S7. Rinse the cable tray treated in step S6 with clean water, then put it into the passivation solution, soak it at room temperature for 2-3 minutes, dry it at 60-80° C. for 1-2 hours, and then age it at 150-200° C. for 3-5 hours.

7. The method for preparing a hot-dip galvanized layer for a cable tray according to claim 6, characterized in that: The degreasing liquid in step S2 is a sodium hydroxide solution with a mass fraction of 8-12%.

8. The method for preparing a hot-dip galvanized layer for a cable tray according to claim 6, characterized in that: In the step S3, an ultrasonic device with a frequency of 20-60 kHz is turned on during the immersion plating.

9. The method for preparing a hot-dip galvanized layer for a cable tray according to claim 6, characterized in that: In the step S6, the mass ratio of nano titanium dioxide to aminosilane coupling agent is 1:

1.

10. The method for preparing a hot-dip galvanized layer for a cable tray according to claim 6, characterized in that: The passivation solution in step S6 is a solution containing 3-5% by mass of sodium chromate and 1-2% by mass of sodium phosphate.